Expected adverse health influences due to exposure to glyphosate-based herbicide (GBH) and its environmental outcomes using Wistar rats as experimental animals - M. I , Abdelgadir; F. I, Omer; M. A , Omer; ElGeed B. A, Awad; MM, Hassan. (International Journal of Medicine, 2023)
A sum of 32 Wistar rats were divided into four equal groups, each containing 8 rats. Study animals were freely subject to normal rodent diet and tap water. One group was put as control. The applied agents were exposed to glyphosate-based herbicide (GBH-400 mg kg–1) GSH (nmol g–1 tissue), (GBH-600 mg kg–1) GSH (nmol g–1 tissue) and (GBH-850 mg kg–1) GSH (nmol g–1 tissue) once per day as oral gavage for 6 weeks. Study results clearly revealed that (GBH) significantly (p≤0.05) decreased the levels of GSH in liver, kidney, and brain tissues, due to many reasons including poor diet, chronic disease, infection and constant stress, besides aging. Biological negative influences of glyphosate herbicide through the scientific community, including government and non-government organizations have increased their interest in detecting and controlling the environmental agents responsible for damages to the human health and sustainability of the ecosystems.